Markers of responsiveness to disopyramide in patients with hypertrophic cardiomyopathy. (15th December 2019) - Habib, Manhal; Hoss, Sara; Bruchal-Garbicz, Beata; Chan, Raymond H.; Rakowski, Harry; Williams, Lynne; Adler, Arnon
Abstract: Background: Significant left-ventricular outflow tract obstruction (LVOTO) in hypertrophic cardiomyopathy (HCM) may result in symptoms and is associated with adverse outcomes. Although disopyramide can reduce resting gradients, nearly 30% of HCM patients do not respond. We sought to study the clinical and echocardiographic variables associated with disopyramide-induced LVOT-gradient reduction. Methods: Forty-one disopyramide-treated HCM patients (average daily-dose 305 mg) were subdivided into two groups: (1) nineteen responders, with a reduction of LVOT-gradients of at least 30% from baseline, and (2) twenty-two non-responders, in whom LVOT-gradients did not change or increased following treatment. All patients had a thorough clinical and echocardiographic assessment pre- and post-treatment initiation. Results: Patients who responded to disopyramide had better pretreatment left ventricular (LV) systolic function (LV ejection fraction of 67.9 ± 5.6% vs. 59.7 ± 5.8%, p = 0.0001), better LV global longitudinal strain (−17.9 ± 2.3% vs. −16.1 ± 2.5%, p = 0.048), less mitral regurgitation, smaller LV size (indexed LV end-systolic volume of 16.2 ± 5.1 ml/m 2 vs. 23.2 ± 6.8 ml/m 2, p = 0.001), and lower LV maximal wall thickness (17.2±3 mm vs.19.2 ± 3.4 mm, p = 0.046). Baseline left atrial (LA) volumes were significantly lower in the responders, with higher indices of LA ejection fraction (62 ± 11.2% vs. 50.5 ± 12.2%, p = 0.005), systolic LA strain (34 ± 12.4% vs. 25.8 ± 10.6%, p = 0.04), and LA strain-rate (1.34 ± 0.49%/sec vs. 0.99 ± 0.24%/sec, p = 0.012). In multivariable analysis, the presence of reduced LV systolic function and systolic LA strain-rate remained independently associated with poor response to disopyramide. Conclusions: Obstructive HCM patients with more severe disease at baseline tend to respond less to disopyramide treatment. In those patients, early referral for alcohol septal ablation or myectomy surgery should be considered. Highlights: Response to disopyramide is associated with better left ventricular function. Response to disopyramide correlates with smaller and better functioning left atrium. Response to disopyramide was not associated with degree of obstruction. Response to disopyramide was not associated with severity of symptoms. These markers can aid in decision making regarding disopyramide therapy.